PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN PADA DUA PULUH LIMA PERUSAHAAN YANG TERDAFTAR DI INDEKS SRI KEHATI 2013 - Setiawan, Temy (Jurnal Akuntansi, 2016)
The problems with the environment which has grabbed the public attention is the main reason for the development of environmental management accounting. Companies need to take parts in this continuous development. One efforts which has been done is to disclose of maintaining environment quality. The cost and benefit of the companies’ activity in responding to environmental issues is regarded as information which needs to be revealed in sustainable reporting. This research is aimed to explore the information of companies’ activity in relation to environmental issues. This research classifies the criteria of environmental costs into four (4) and analyses the companies indexed in SRI KEHATI. This is a qualitative research. The researcher conducts an analysis on 25 companies listed in 2013 SRI KEHATI index. This research finds that the most common activities conducted by the companies in taking their responsibilities to the environment is in waste management, energy efficiency, and nature preservation (in relation to biodiversity). There are only four (4) companies which have devoted most of their activities to environmental issues; Bank Negara Indonesia (Persero) Tbk, Tambang Batu Bara Bukit Asam (Persero) Tbk, Telelomunikasi Indonesia (Persero) Tbk, and United Tractors Tbk. The common criteria employed is preventive cost.